2021
DOI: 10.1371/journal.pone.0249868
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate n-variability (HRnV) measures for prediction of mortality in sepsis patients presenting at the emergency department

Abstract: Sepsis is a potentially life-threatening condition that requires prompt recognition and treatment. Recently, heart rate variability (HRV), a measure of the cardiac autonomic regulation derived from short electrocardiogram tracings, has been found to correlate with sepsis mortality. This paper presents using novel heart rate n-variability (HRnV) measures for sepsis mortality risk prediction and comparing against current mortality prediction scores. This study was a retrospective cohort study on patients present… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Unlike another study which found higher risk among neonates (11), we found a significant proportion of SBIs (77%) in the group 29-90 days old, highlighting the need for careful assessment and monitoring for all young infants <90 days old. An earlier study among adults presenting to the ED with sepsis demonstrated that HRnV in addition to HRV parameters and vital signs, was superior in predicting for mortality when compared to traditional scores including the acute physiology and chronic health evaluation II (APACHE II) and sequential organ failure assessment (SOFA) (27). The authors propose that HRnV may contribute to rapid, objective and accurate risk stratification for sepsis severity and risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Unlike another study which found higher risk among neonates (11), we found a significant proportion of SBIs (77%) in the group 29-90 days old, highlighting the need for careful assessment and monitoring for all young infants <90 days old. An earlier study among adults presenting to the ED with sepsis demonstrated that HRnV in addition to HRV parameters and vital signs, was superior in predicting for mortality when compared to traditional scores including the acute physiology and chronic health evaluation II (APACHE II) and sequential organ failure assessment (SOFA) (27). The authors propose that HRnV may contribute to rapid, objective and accurate risk stratification for sepsis severity and risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study among adults presenting to the ED with sepsis demonstrated that HRnV in addition to HRV parameters and vital signs, was superior in predicting for mortality when compared to traditional scores including the acute physiology and chronic health evaluation II (APACHE II) and sequential organ failure assessment (SOFA) ( 27 ). The authors propose that HRnV may contribute to rapid, objective and accurate risk stratification for sepsis severity and risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations